ANALISIS RASIO LIKUIDITAS TERHADAP PROFITABILITAS PADA PT BANK BJB Tbk PERIODE 2014-2016 - KARYADI; LUKMAN NULHAKIM (EKBIS (Ekonomi & Bisnis), 2018)
This study is aimed to determine how the result analysis of ratio liquidity on profitability at PT Bank Pembangunan Daerah Jawa Barat dan Banten period of 2014-2016. The research method used descriptive research method with quantitative approach, while data collection techniques used the analysis of correlation coefficients person product moment and coefficients of determination. Based on data research result, it could concluded that the ratio of liquidity on profitability had a strong relationship as much as 0,740, while the influence was 54,8%. The writer suggests: 1) need to maintain current assets owned primarily in the form of cash and cash equivalents 2) need to suppress the increase in operating expenses.